A preparation method and application of LLZO solid electrolyte

By using LLASMZ glass sintering additives and mechanical activation technology, the problem of densification of LLZO solid electrolyte sintering and volatility of Li elements is solved, high density and stability are achieved, and its electrochemical performance is improved.

CN118930268BActive Publication Date: 2025-04-18WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411221255.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-04-18
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

During the sintering process, LLZO solid electrolyte has problems such as difficulty in densification, high sintering temperature and large volatility of Li elements, resulting in uncontrollable components and unstable electrochemical properties.

Method used

Li2O-Al2O3-SiO2-MgO-La2O3-ZrO2 glass sintering additive (LLASMZ) was used to prepare nano-scale glass sintering additives by sol-gel method, and combined with mechanical activation technology, it reduces the sintering temperature and improves the density and ionic conductivity of the ceramics.

Benefits of technology

The LLZO solid electrolyte is achieved with high density and stability at low sintering temperature, reducing the volatility of Li elements, improving its ionic conductivity and the stability of cubic phase at room temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118930268B_ABST
    Figure CN118930268B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of solid electrolyte ceramic materials, and in particular to a preparation method and application of LLZO solid electrolyte. The specific implementation steps are: 1. Prepare LLASMZ glass sintering aid according to the sol-gel process; 2. 7‑ 3x Al x La3Zr2O 12 1. Weigh the Li source, La2O3, Al2O3 and ZrO2 in a stoichiometric ratio, ball-mill and mix them evenly; dry, sieve and press the evenly mixed powder into blocks for initial calcination in a silicon carbon rod furnace; 3. Add the powder after initial calcination, glass sintering aid, water and ball mill into a planetary ball mill for mechanical activation; 4. Mix the activated powder with a binder and granulate to form; after debinding, cover the green body with LLZO powder of the same composition, place it in a crucible for sealed sintering to obtain the desired LLZO solid electrolyte. The present invention combines a mechanical activation auxiliary process with the addition of a sintering aid to develop a preparation method that enables LLZO solid electrolytes to obtain high stability and density at low sintering temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolyte ceramic materials, and in particular to a preparation method and application of a LLZO solid electrolyte. Background Art

[0002] Solid-state batteries are a new type of battery that uses solid electrolytes to replace the organic electrolytes in traditional lithium-ion batteries. They have the advantages of high energy density and high safety, and are expected to replace traditional lithium-ion batteries. Currently, commonly used solid electrolytes include polymer solid electrolytes, oxide solid electrolytes, sulfide solid electrolytes, and halide solid electrolytes. Among them, garnet-type oxides Li7La3Zr2O 12 (LLZO) solid electrolyte has a wide voltage window (0~6V vs.Li / Li + ), higher ionic conductivity (2.4×10 -4 ), low ion migration activation energy and good chemical stability to metallic lithium, making it one of the most promising solid electrolytes for all-solid-state battery applications. However, in actual applications, LLZO solid electrolytes have problems such as difficulty in sintering densification (LLZO electrolyte has poor sintering activity and is difficult to densify by conventional sintering), high sintering temperature (sintering temperature is as high as 1280°C) and long sintering time. This will cause a large amount of volatilization of Li elements in the LLZO system, affecting the stoichiometric ratio, and thus causing uncontrollable LLZO composition, unstable phase structure and electrochemical performance. At the same time, it is difficult to prepare high-density LLZO solid electrolytes by conventional buried powder sintering methods.

[0003] Introducing sintering aids into LLZO solid electrolytes is a common method to improve the density of ceramics. Li3BO3 (melting point 760°C), Li4SiO4 (melting point 1255°C), LiZrO3 (melting point 720°C) and Li3PO4 (melting point 837°C) are widely used as LLZO ceramic sintering aids, but these sintering aids generally have high melting points and can only form a glass phase at a higher temperature. Although they can promote the densification process of solid electrolytes, the residual crystalline sintering aids will be enriched at the grain boundaries and hinder the conduction of lithium ions.

[0004] Therefore, there is an urgent need to develop a method that can enable LLZO solid electrolyte to obtain high stability and high density at low sintering temperature. Summary of the invention

[0005] In order to solve at least one of the above problems, the first aspect of the present invention provides a LLASMZ glass sintering aid, wherein the LLASMZ glass sintering aid is Li2O-Al2O3-SiO2-MgO-La2O3-ZrO2 glass.

[0006] According to a specific embodiment of the present invention, in the LLASMZ glass sintering aid, the molar ratio of the elements Li:Al:Si:Mg:La:Zr is (1-2):(3.5-4.9):(9.15-11.6):0.4:(0.9-1.5):(0.1-0.4).

[0007] According to a specific embodiment of the present invention, the particle size of the LLASMZ glass sintering aid is 200-300 nm.

[0008] The second aspect of the present invention provides a method for preparing a LLASMZ glass sintering aid, comprising:

[0009] S1, dissolving lithium acetate, aluminum acetate, silicon acetate, magnesium acetate, lanthanum acetate and zirconium acetate in anhydrous ethanol respectively, heating and stirring to form a sol containing different components;

[0010] S2, mixing and stirring the sol containing different components prepared in step S1, and drying to obtain a xerogel;

[0011] S3, heat-treating the dry gel to obtain LLASMZ glass.

[0012] According to a specific embodiment of the present invention, in step S2, the lithium acetate, aluminum acetate, silicon acetate, magnesium acetate, lanthanum acetate and zirconium acetate are added according to the molar ratio of the elements Li:Al:Si:Mg:La:Zr of (1-2):(3.5-4.9):(9.15-11.6):0.4:(0.9-1.5):(0.1-0.4).

[0013] According to a specific embodiment of the present invention, the temperature of the heating and stirring is 40 to 50° C., and the stirring time is 1 to 3 hours.

[0014] According to a specific embodiment of the present invention, in step S2, the drying temperature is 60-80°C.

[0015] According to a specific embodiment of the present invention, in step S3, the temperature of the heat treatment is 450-550°C.

[0016] The third aspect of the present invention provides the use of the LLASMZ glass sintering aid described in the first aspect in the preparation of LLZO solid electrolyte.

[0017] A fourth aspect of the present invention provides a method for preparing a LLZO solid electrolyte, comprising:

[0018] A. According to chemical composition Li 7-3x Al x La3Zr2O 12Li source, La2O3, ZrO2 and Al2O3 are weighed in a stoichiometric ratio, and are ground, mixed, dried, sieved, pressed into blocks and calcined in sequence;

[0019] B. adding the sintering aid described in the first aspect of the present invention to the powder calcined in step A to obtain a mixed powder;

[0020] C. adding water to the mixed powder and performing mechanical activation together with a ball mill;

[0021] D. Mixing the mechanically activated mixed powder with a binder and granulating, molding, and debinding the mixed powder, and then using LLZO powder of the same composition to cover the green body, sintering, and obtaining the LLZO solid electrolyte

[0022] in,

[0023] In step A, 0.15≤x≤0.25.

[0024] According to a specific embodiment of the present invention, in step A, the Li source includes at least one of Li2CO3, Li2O or LiOH.

[0025] According to a specific embodiment of the present invention, the calcination temperature is 900-950° C., and the calcination time is 2-4 hours.

[0026] According to a specific embodiment of the present invention, in step B, the mass percentage of the sintering aid in the mixed powder is 0.5-1%.

[0027] According to a specific embodiment of the present invention, in step C, the mass ratio of the mixed powder to water and ball mill is 1:1:(10-40), and the ball mill includes a zirconium oxide ball mill and / or an aluminum oxide ball mill.

[0028] According to a specific embodiment of the present invention, in step D, the particle size of the powder after mechanical activation is no greater than 0.5 μm.

[0029] According to a specific embodiment of the present invention, in step D, the binder is a polyvinyl alcohol solution with a mass fraction of 5 to 10%, and the added amount accounts for 0.3 to 0.5% of the mass percentage of the mixed powder.

[0030] According to a specific embodiment of the present invention, in step D, the debinding temperature is 500-600° C., the heating rate is 1-2° C. / min, and the debinding time is 2-4 h.

[0031] According to a specific embodiment of the present invention, in step D, the sintering temperature is 900-950° C., and the sintering time is 2-4 hours.

[0032] A fifth aspect of the present invention provides a LLZO solid electrolyte, which is prepared by the method described in the fourth aspect.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention aims at the application problem of LLZO being difficult to sinter and having high sintering temperature. The high energy of the planetary ball mill is used to fully crush the LLZO powder, while reducing the particle size of the LLZO powder, increasing the specific surface area and defects of the LLZO powder, thereby enhancing the sintering activity of the powder, facilitating the low-temperature sintering of the LLZO powder, and reducing the volatilization of the Li element. On the other hand, compared with traditional sintering aids, the nanoscale Li2O-Al2O3-SiO2-MgO-La2O3-ZrO2 glass sintering aid prepared by the sol-gel method has a lower glass transition temperature, can form a large amount of glass phase at 500-550°C, and promote the sintering of the LLZO electrolyte. In addition, compared with crystalline sintering aids, amorphous Li-Al-Si glass has higher ionic conductivity, and can effectively improve the total ionic conductivity of the LLZO solid electrolyte when enriched at the grain boundary. Finally, in order to address the problems of instability of the cubic phase of LLZO solid electrolyte and uneven grain growth during liquid phase sintering, the present invention introduces Al2O3 to dope the LLZO lattice at the Li site, increase Li defects, improve the ionic conductivity of the LLZO solid electrolyte and the stability of the cubic phase at room temperature, and introduces MgO into the sintering aid to reduce the migration rate of the grain boundaries during ceramic sintering to achieve the purpose of grain refinement. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 XRD pattern of the LLZO solid electrolyte prepared in Example 1 of the present invention;

[0037] Figure 2 This is a SEM image of the LLZO solid electrolyte prepared in Example 1 of the present invention;

[0038] Figure 3 This is the impedance spectrum of the LLZO solid electrolyte prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0040] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.

[0041] In this document, the terms “contain”, “include” or “comprise” are open expressions, that is, they include the contents specified in the present invention but do not exclude other contents.

[0042] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.

[0043] In this article, the term "mechanical chemical activation" refers to a process in which minerals undergo lattice distortion and local damage under the action of mechanical forces, and form various defects, which increase their internal energy and enhance their reaction activity, thereby enabling the leaching of minerals at lower leaching concentrations and temperatures.

[0044] The present invention provides a method for preparing a mechanical activation-assisted low-temperature sintering LLZO solid electrolyte. The method can achieve sintering at a relatively low temperature of 900-950° C. when preparing the LLZO solid electrolyte. The sintered LLZO solid electrolyte has high density and ion mobility, and can meet the application requirements of the LLZO solid electrolyte.

[0045] In order to solve the technical problem proposed by the present invention, the present invention provides a method for preparing a mechanical activation-assisted low-temperature sintering LLZO solid electrolyte, wherein the method uses ywt% LLASMZ glass to prepare a Li 7-3x Al x La3Zr2O 12 A solid electrolyte, wherein 0.15≤x≤0.25; y is the amount of LLASMZ glass added.

[0046] The present invention provides a method for preparing an LLASMZ glass sintering aid for LLZO solid electrolyte, which specifically comprises the following steps:

[0047] 1) dissolving lithium acetate, aluminum acetate, silicon acetate, magnesium acetate, lanthanum acetate and zirconium acetate in anhydrous ethanol respectively, heating and stirring to form a sol;

[0048] 2) mixing and stirring the sols of each group to form a mixed sol, and drying to obtain a xerogel;

[0049] 3) The dry gel is heat treated in a muffle furnace to obtain LLASMZ glass.

[0050] Among them, the specific composition of LLASMZ is Li2O-Al2O3-SiO2-MgO-La2O3-ZrO2 glass, and the molar ratio of each element is Li:Al:Si:Mg:La:Zr=(1~2):(3.5~4.9):(9.15~11.6):0.4:(0.9~1.5):(0.1~0.4); the heating and stirring temperature is 40~50℃, and the stirring time is 1~3h; the drying temperature is 60~80℃; the heat treatment temperature is 450~550℃; the particle size of the LLASMZ glass sintering aid is 200~300nm.

[0051] The present invention provides a method for preparing a mechanical activation-assisted low-temperature sintering LLZO solid electrolyte, which specifically comprises the following steps:

[0052] S1, by chemical composition Li 7-3x Al x La3Zr2O 12 Weighing Li source, La2O3, ZrO2 and Al2O3 in a stoichiometric ratio, ball-milling and mixing uniformly; drying, sieving and pressing the uniformly mixed powder into blocks, and performing primary calcination in a silicon carbon rod furnace;

[0053] S2, adding the powder after primary calcination, water, glass sintering aid and ball mill into a planetary ball mill for mechanical activation;

[0054] S3, mixing the activated powder with a binder and granulating and molding; after debinding, using LLZO powder of the same composition to cover the green body, and placing it in a crucible for sealed sintering to obtain the desired LLZO solid electrolyte.

[0055] In the above scheme, in step S1, water: material: ball mill = 1:1:3.

[0056] In the above scheme, in step S1, the rotation speed of the ball mill is 200 r / min.

[0057] In the above scheme, in step S1, the ball milling mixing time is 24 to 48 hours.

[0058] In the above scheme, in step S1, the sieving is through a 80-100 mesh sieve.

[0059] In the above scheme, in step S1, the Li source is one or more of Li2CO3, Li2O or LiOH.

[0060] In the above scheme, in step S1, the excess amount of Li source is 7wt% to 10wt%, and the specific excess amount depends on the temperature and time of the calcination and sintering steps.

[0061] In the above scheme, the calcination temperature is 900-950°C and the calcination time is 2-4h. The purpose of this step is to make the mixed powder undergo solid phase reaction to synthesize the desired LLZO phase. The solid phase reaction temperature should not be too high and the reaction time should not be too long. Too high or too long temperature can easily lead to excessive volatilization of Li, thereby causing the stoichiometric ratio of the LLZO system to deviate and cause unstable performance; when the solid phase reaction temperature is too low or the reaction time is too short, the solid phase reaction is not sufficient.

[0062] In the above scheme, in step S2, the activation time is 24 to 48 hours.

[0063] In the above scheme, in step S2, material: water: ball mill = 1:1:10-40.

[0064] In the above scheme, in step S2, the rotation speed of the ball mill is 400r / min.

[0065] In the above scheme, in step S2, the particle size of the powder after mechanical activation treatment is ≤0.5 μm.

[0066] In the above scheme, in step S2, the amount of glass sintering aid added is 0.5-1 wt%.

[0067] In the above scheme, in step S3, the binder is a polyvinyl alcohol solution with a mass fraction of 5 to 10%, and the added amount is 0.3 to 0.5% of the mass of the powder.

[0068] In the above scheme, in step S3, the debinding temperature is 500-600°C, the heating rate is 1-2°C / min, and the debinding time is 2-4h; the sintering temperature is 900-950°C, and the sintering time is 2-4h.

[0069] The main chemical reagents used in this application and their purchase sources are shown in Table 1.

[0070] Table 1

[0071] Reagent name Part Number Where to buy Lithium acetate L102779 Aladdin Aluminum Acetate A742515 Aladdin Silicone Acetate S283291 Aladdin Magnesium acetate M108880 Aladdin Lanthanum acetate L106123 Aladdin Zirconium acetate Z110957 Aladdin Lithium carbonate 20022817 Sinopharm Reagents Lanthanum Oxide 52003861 Sinopharm Reagents Alumina 10000917 Sinopharm Reagents Zirconia 51028960 Sinopharm Reagents Ball Mill Hanhe-95 zirconia ball Shandong Hanhe New Materials Co., Ltd.

[0072] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the art or the product instructions are used. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the art without making creative work are within the scope of protection of the present invention.

[0073] Example 1

[0074] The LLZO solid electrolyte in this embodiment has a chemical composition of:

[0075] Li 6.55 Al 0.15 La3Zr2O 12 +0.5wt% LLASMZ glass.

[0076] 1. Preparation of sintering aid LLASMZ glass

[0077] Lithium acetate, aluminum acetate, silicon acetate, magnesium acetate, lanthanum acetate and zirconium acetate are weighed and dissolved in anhydrous ethanol at 40° C. according to a molar ratio of Li:Al:Si:Mg:La:Zr of 1:4:10:0.4:1:0.1, and stirred to form a sol; each group of sols is mixed and stirred to form a mixed sol, and dried at 60° C. to obtain a dry gel; finally, the dry gel is heat-treated at 450° C. in a muffle furnace to obtain the desired LLASMZ glass.

[0078] 2. Preparation of LLZO solid electrolyte

[0079] S1, by chemical composition Li 6.55 Al 0.15 La3Zr2O 12 Li2CO3 (7 wt% excess), La2O3, Al2O3 and ZrO2 were weighed in a stoichiometric ratio, and each raw material was ball-milled for 24 hours in a mass ratio of material: deionized water: ball mill = 1:1:3 to mix them evenly; the evenly mixed powder was dried, passed through an 80-mesh sieve, and pressed into blocks under a pressure of 10 MPa; finally, it was placed in a silicon carbon rod furnace and calcined at 900°C for 2 hours.

[0080] S2, the calcined powder was mixed with the sintering aid LLASMZ glass, deionized water and ball mill in a mass ratio of 1:1:20, and added into a planetary ball mill for mechanical activation for 24 hours.

[0081] S3, mixing the activated powder with 7wt% polyvinyl alcohol binder (0.3wt% of the powder mass added) and granulating, and finally pressing and molding in a steel mold to obtain a green body; using LLZO powder of the same composition to cover the green body, and placing it in a crucible to seal, debind and sinter to obtain the required LLZO solid electrolyte.

[0082] S3, mixing the activated powder with a binder and granulating and molding; after debinding at 550°C, using LLZO powder of the same composition to cover the green body, and placing it in a crucible for sealed sintering at a sintering temperature of 900°C and keeping warm for 2 hours to obtain the desired LLZO solid electrolyte.

[0083] The prepared LLZO solid electrolyte was subjected to X-ray diffraction, and the results are as follows: Figure 1 As shown, the LLZO solid electrolyte synthesized in this embodiment has a pure cubic phase structure, and no impurities such as ZrO2 and Al2O3 are detected, indicating that the raw materials have been fully reacted, and Al2O3 as a dopant is completely dissolved in the LLZO lattice. At the same time, the peak at 2degree = 27.4° does not show obvious splitting phenomenon, indicating that Al2O3 Li-doping can increase Li + defects, improving the stability of the cubic phase at room temperature.

[0084] The prepared LLZO solid electrolyte was scanned by electron microscope, and the results are as follows: Figure 2 As shown, the LLZO solid electrolyte synthesized in this embodiment has a higher density, and intergranular fracture and transgranular fracture coexist, among which intergranular fracture is the main fracture form, showing obvious liquid phase sintering characteristics, indicating that the sintering aid formed by LLASMZ glass effectively promotes the sintering of LLZO solid electrolyte.

[0085] The impedance test of the prepared LLZO solid electrolyte was carried out, and the results are as follows Figure 3 As shown, the LLZO solid electrolyte synthesized in the embodiment has a lower impedance value. The working principle of electrochemical impedance spectroscopy is: by applying a small sinusoidal signal to the electrode, the equilibrium potential of the electrode is slightly disturbed; by analyzing the corresponding current parameters measured, the electrochemical impedance spectrum of the electrode is calculated; using a suitable equivalent circuit to fit and analyze the electrochemical impedance spectrum, the electrochemical performance parameters of the electrode and the electrode response process are studied.

[0086] The present invention adopts electrochemical impedance spectroscopy to test the total resistance of the solid electrolyte sheet, and the test conditions are: the test frequency range is 1-7MHz, the sine voltage amplitude is 50mV, and the test software is Zview 3.0.

[0087] Example 2

[0088] The LLZO solid electrolyte in this embodiment has a chemical composition of:

[0089] Li 6.4 Al 0.20 La3Zr2O 12 +0.7wt% LLASMZ glass.

[0090] 1. Preparation of sintering aid LLASMZ glass

[0091] Lithium acetate, aluminum acetate, silicon acetate, magnesium acetate, lanthanum acetate and zirconium acetate are weighed and dissolved in anhydrous ethanol at 45° C. according to the ratio of Li:Al:Si:Mg:La:Zr=1.5:4.5:10.5:0.4:1.2:0.2, and stirred to form a sol; each group of sols is mixed and stirred to form a mixed sol, and dried at 70° C. to obtain a dry gel; finally, the dry gel is heat-treated at 500° C. in a muffle furnace to obtain the desired LLASMZ glass.

[0092] 2. Preparation of LLZO solid electrolyte

[0093] S1, by chemical composition Li 6.4 Al 0.20 La3Zr2O 12 Li2CO3 (8 wt% excess), La2O3, Al2O3 and ZrO2 were weighed in a stoichiometric ratio, and each raw material was ball-milled for 24 hours in a mass ratio of material: deionized water: ball mill = 1:1:3 to mix them evenly; the evenly mixed powder was dried, passed through an 80-mesh sieve, and pressed into blocks under a pressure of 10 MPa; finally, it was placed in a silicon carbon rod furnace and calcined at 950°C for 3 hours.

[0094] S2, the calcined powder was mixed with the sintering aid LLASMZ glass, and then mixed with deionized water and ball mill in a mass ratio of 1:1:30 and added into a planetary ball mill for mechanical activation for 30 hours.

[0095] S3, mixing the activated powder with 10wt% polyvinyl alcohol binder (0.4wt% of the powder mass) and granulating it, and finally pressing it in a steel mold to obtain a green body; using LLZO powder of the same composition to cover the green body, and placing it in a crucible to seal, debind and sinter to obtain the required LLZO solid electrolyte.

[0096] S3, mixing the activated powder with a binder and granulating and molding; after debinding at 500°C, using LLZO powder of the same composition to cover the green body, and placing it in a crucible for sealed sintering at a sintering temperature of 950°C and keeping it warm for 4 hours to obtain the desired LLZO solid electrolyte.

[0097] Example 3

[0098] The LLZO solid electrolyte in this embodiment has a chemical composition of:

[0099] Li 6.25 Al 0.25 La3Zr2O 12 +1wt% LLASMZ glass.

[0100] Lithium acetate, aluminum acetate, silicon acetate, magnesium acetate, lanthanum acetate and zirconium acetate are weighed and dissolved in anhydrous ethanol at 50° C. according to the ratio of Li:Al:Si:Mg:La:Zr=2:4.9:11:0.4:1.5:0.3, respectively, and stirred to form a sol; each group of sols is mixed and stirred to form a mixed sol, and dried at 80° C. to obtain a dry gel; finally, the dry gel is heat-treated at 550° C. in a muffle furnace to obtain the desired LLASMZ glass.

[0101] The preparation method of the LLZO solid electrolyte in this embodiment comprises the following steps:

[0102] S1, by chemical composition Li 6.25 Al 0.25 La3Zr2O 12 Li2CO3 (excess 10wt%), La2O3, Al2O3 and ZrO2 were weighed in a stoichiometric ratio, and each raw material was ball-milled for 24 hours in a mass ratio of material: deionized water: ball mill = 1:1:3 to mix them evenly; the evenly mixed powder was dried, passed through an 80-mesh sieve, and pressed into blocks under a pressure of 10Mpa; finally, it was placed in a silicon carbon rod furnace and calcined at 950°C for 4h.

[0103] S2, the calcined powder was mixed with LLASMZ glass, and then mixed with deionized water and ball mill in a mass ratio of 1:1:40 and added into a planetary ball mill for mechanical activation for 15 h.

[0104] S3, mixing the activated powder with 10wt% polyvinyl alcohol binder (0.5wt% of the powder mass) and granulating it, and finally pressing it in a steel mold to obtain a green body; using LLZO powder of the same composition to cover the green body, and placing it in a crucible to seal, debind and sinter to obtain the required LLZO solid electrolyte.

[0105] S3, mixing the activated powder with a binder and granulating and molding; after debinding at 550°C, the green body is covered with LLZO powder of the same composition, and sealed and sintered in a crucible at a sintering temperature of 950°C for 4 hours to obtain the desired LLZO solid electrolyte.

[0106] Comparative Example 1

[0107] The only difference between Comparative Example 1 and Example 1 is that no sintering aid is added to S2.

[0108] Comparative Example 2

[0109] The difference between Comparative Example 2 and Example 1 is that the amount of sintering aid added in S2 is 0.1 wt %.

[0110] Comparative Example 3

[0111] The only difference between Comparative Example 3 and Example 1 is that the amount of sintering aid added in S2 is 2 wt %.

[0112] Comparative Example 4

[0113] The only difference between Comparative Example 4 and Example 1 is that the sintering aid in S2 is Li3PO4.

[0114] Comparative Example 5

[0115] The only difference between Comparative Example 5 and Example 1 is that the sintering aid in S2 is Li4SiO4.

[0116] Comparative Example 6

[0117] The only difference between Comparative Example 6 and Example 1 is that the sintering aid in S2 is LiBiO2.

[0118] Comparative Example 7

[0119] The only difference between Comparative Example 7 and Example 1 is that mechanical activation is not performed in S2. In this step, the mass ratio of the mixture of powder and sintering aid to deionized water and ball mill is 1:1:3.

[0120] Comparative Example 8

[0121] Comparative Example 8 The only difference between Example 1 and Comparative Example 8 is that the LLASMZ glass is prepared by the conventional solid phase method. The conventional solid phase method preparation process of the LLASMZ glass is as follows:

[0122] Lithium carbonate, aluminum oxide, silicon oxide, magnesium oxide, lanthanum oxide and zirconium oxide were weighed according to the ratio of Li:Al:Si:Mg:La:Zr=2:4.9:11:0.4:1.5:0.3, added into a ball mill and ball milled for 24 hours to make the materials evenly mixed and dried to pass through an 80-mesh sieve; the dried materials were melted at 1500°C in a high-temperature frit furnace and prepared into amorphous glass by water quenching; the amorphous glass was crushed into glass powder by a planetary ball mill.

[0123] Comparative Example 9

[0124] The only difference between Comparative Example 9 and Example 1 is that the LLASMZ glass formula does not contain MgO.

[0125] Comparative Example 10

[0126] The only difference between Comparative Example 10 and Example 1 is that the LLASMZ glass formula does not contain Al2O3.

[0127] Comparative Example 11

[0128] The only difference between Comparative Example 11 and Example 1 is that the LLASMZ glass formula does not contain SiO2.

[0129] The lowest sintering temperature of the LLZO solid electrolyte prepared in each embodiment and each comparative example, and the performance test of the prepared LLZO solid electrolyte material were performed, and the results are shown in Table 2.

[0130] ρ l It is the relative volume density and is tested using the Archimedes drainage method combined with jade software.

[0131] R is the total impedance of the solid electrolyte (the real axis value at the inflection point of the semicircle in the impedance spectrum), which is measured by forming a blocking cell by gold spraying on both sides of the solid electrolyte in combination with an electrochemical workstation.

[0132] σ is the ionic conductivity, which can be calculated by the following formula:

[0133]

[0134] Wherein, σ is the total ionic conductivity of the solid electrolyte (S / cm);

[0135] R is the total impedance of the solid electrolyte (Ω);

[0136] r is the diameter of the solid electrolyte ceramic (cm);

[0137] d is the thickness of the solid electrolyte (cm).

[0138] Table 2

[0139]

[0140]

[0141] As can be seen from Table 2, Examples 1 to 3 have smaller impedance, high relative density and ionic conductivity, while Comparative Examples 1 to 2 have low relative density, resulting in LLZO solid electrolytes having higher impedance and low ionic conductivity, which indicates that mechanical activation can increase the surface energy of the powder and the combination of defects with LLASMZ glass sintering aids to effectively promote the sintering of LLZO solid electrolytes and maintain excellent electrochemical properties; Comparative Example 3 has a higher density, but the amount of sintering aid added is too high, resulting in a large amount of glass phase enriched in the material, which is not conducive to the improvement of ionic conductivity; Comparative Examples 4 to 6 use traditional oxides or silicates as sintering aids. Although it has been reported that such sintering aids can effectively promote the sintering of LLZO ceramics, at lower sintering temperatures, such sintering aids produce less liquid phase, and the effect of promoting ceramic sintering is limited; After removing the mechanical activation step, Comparative Example 7 is compared with Example 1 , the density of the ceramic is significantly reduced, indicating that mechanical activation can effectively increase the driving force of ceramic sintering and promote the sintering of LLZO ceramics; Comparative Example 8 uses the traditional solid-phase method to prepare LLASMZ glass. Since the glass particle size prepared by the solid-phase method can only reach the micron level, the temperature of generating the liquid phase during the sintering process is relatively high, and the effect of promoting LLZO ceramics is not as good as the LLASMAZ glass prepared by the sol-gel method; in comparisons 9 to 11, Comparative Example 9 lacks MgO. During the sintering process of LLZO ceramics, the grains grow excessively, resulting in more pores around the grains, affecting the mechanical and electrical properties of the ceramics. Comparative Example 10 lacks Al2O3. Although it can promote the sintering of ceramics, the ionic conductivity of the liquid phase residue formed after sintering is poor, which affects the ionic conductivity of LLZO. Comparative Example 11 does not contain SiO2. Due to the lack of glass network formers, the prepared sintering aid does not form glass, and the introduced sintering aid does not promote the sintering of LLZO ceramics.

[0142] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A LLASMZ glass sintering aid, characterized in that: The LLASMZ glass sintering aid is Li2O-Al2O3-SiO2-MgO-La2O3-ZrO2 glass; In the LLASMZ glass sintering aid, the molar ratio of the elements Li:Al:Si:Mg:La:Zr is (1-2):(3.5-4.9):(9.15-11.6):0.4:(0.9-1.5):(0.1-0.4); The particle size of the LLASMZ glass sintering aid is 200-300 nm.

2. A method for preparing a LLASMZ glass sintering aid, characterized in that: include: S1, dissolving lithium acetate, aluminum acetate, silicon acetate, magnesium acetate, lanthanum acetate and zirconium acetate in anhydrous ethanol respectively, heating and stirring to form a sol containing different components; S2, mixing and stirring the sol containing different components prepared in step S1, and drying to obtain a xerogel; S3, heat-treating the dry gel to obtain LLASMZ glass; In step S2, the lithium acetate, aluminum acetate, silicon acetate, magnesium acetate, lanthanum acetate, and zirconium acetate are added in a molar ratio of Li:Al:Si:Mg:La:Zr of (1-2):(3.5-4.9):(9.15-11.6):0.4:(0.9-1.5):(0.1-0.4); The heating and stirring temperature is 40-50°C, and the stirring time is 1-3h; In step S2, the drying temperature is 60-80°C; In step S3, the temperature of the heat treatment is 450-550°C.

3. Use of the LLASMZ glass sintering aid according to claim 1 in the preparation of LLZO solid electrolyte.

4. A method for preparing LLZO solid electrolyte, characterized in that: include: A. According to chemical composition Li 7-3x Al x La3Zr2O 12 Li source, La2O3, ZrO2 and Al2O3 are weighed in a stoichiometric ratio, and are ground, mixed, dried, sieved, pressed into blocks and calcined in sequence; B. adding the sintering aid according to claim 1 to the powder calcined in step A to obtain a mixed powder; C. adding water to the mixed powder and performing mechanical activation together with a ball mill; D. Mixing the mechanically activated mixed powder with a binder and granulating, molding, and debinding the mixed powder, and then using LLZO powder of the same composition to cover the green body, sintering, and obtaining the LLZO solid electrolyte in, In step A, 0.15≤x≤0.

25.

5. The method according to claim 4, characterized in that In step A, the Li source includes at least one of Li2CO3, Li2O or LiOH; The calcination temperature is 900-950° C., and the calcination time is 2-4 hours.

6. The method according to claim 4, characterized in that In step B, the mass percentage of the sintering aid in the mixed powder is 0.5-1%; In step C, the mass ratio of the mixed powder to water and ball mill is 1:1:(10-40), and the ball mill includes a zirconium oxide ball mill and / or an aluminum oxide ball mill.

7. The method according to claim 4, characterized in that In step D, the particle size of the powder after mechanical activation is no greater than 0.5 μm; The binder is a polyvinyl alcohol solution with a mass fraction of 5 to 10%, and the added amount accounts for 0.3 to 0.5% of the mass percentage of the mixed powder; The debinding temperature is 500-600°C, the heating rate is 1-2°C / min, and the debinding time is 2-4h; The sintering temperature is 900-950° C., and the sintering time is 2-4 hours.

8. A LLZO solid electrolyte, characterized in that: Prepared by the method described in any one of claims 4 to 7.

Citation Information

Patent Citations

  • Nano glass powder and use thereof, particularly multicomponent glass powder with a mean particle size of less than 1 [mu]m

    CN101094818A

  • Lithium-enriched anti-perovskite sulfides, solid electrolyte material containing lithium-enriched anti-perovskite sulfides and application of solid electrolyte material

    CN104466239A